On the Issue of the Parthian Pahlavs' Socio-Political Nature - Arthur Melikyan (Banber Arevelagitut'yan Instituti, 2025)
The role of the high aristocracy, the so-called pahlavs, is undeniable in the history of the Parthian state. In the second half of III century BC the assistance of the pahlavs to the Arsacid dynasty considerably contributed to the establishment of the Dahae and organization of their own state in Parthia and Hyrcania. During the following centuries the rises and crises of the political life of the Parthian statehood and even its final decline in the first quarter of the III century was due to the attitude of the Parthian pahlavs towards the Arsacid dynasty. In spite of the key role of the pahlavs, the issues of their ethnic origin, social nature, their number and the relations with the royal power are still poorly studying in historical science. We hope that this article will bring its contribution in studying the history of the Parthian pahlavs.